Analisis Kesalahan Ejaan yang Disempurnakan (EYD) dalam Proposal Skripsi Mahasiswa - Ummul Khair (ESTETIK : Jurnal Bahasa Indonesia, 2018)
This text study objective was to determine how much the level of student writing errors made in the use of written language in developing a thesis proposal. The method used in the research data penganalisissan this text is the text method , which collects a number of text samples, further reading and doing analyzing student writing done , and also uses descriptive method of analysis. As the results, 1) error writing uppercase (capital) in the student proposal STAIN Curup VIII semester of academic year 2012/2013 as many as 850 words, with a percentage of 40.59 %; 2) error writing spelling on student proposals STAIN Curup VIII semester of academic year 2012/2013 as many as 681 words, with a percentage of 32, 52 %; 3) error writing prepositions (di, ke and dari) the student proposal STAIN Curup VIII semester of academic year 2012/2013 as many as 282 words, with a percentage of 13.46 %; 4) error writing punctuation dot (.), comma (,), colon (:), semicolon (;), and quotes (") on student proposals as many as 281 words, with a percentage of 13.41 %.